Strategy for designing selective α-l-rhamnosidase inhibitors: Synthesis and biological evaluation of l-DMDP cyclic isothioureas. Issue 1 (1st January 2017) - Miyawaki, Shota; Hirokami, Yuki; Kinami, Kyoko; Hoshino, Masako; Minehira, Daisuke; Miyamoto, Daiki; Nash, Robert J.; Fleet, George W.J.; Adachi, Isao; Toyooka, Naoki; Kato, Atsushi
Graphical abstract: Abstract: This study shows that the cyclization ofl -DMDP thioureas to bicyclicl -DMDP isothioureas improved α-l -rhamnosidase inhibition which was further enhanced by increasing the length of the alkyl chain. The addition of a long alkyl chain, such as decyl or dodecyl, to the nitrogen led to the production of highly potent inhibitors of α-l -rhamnosidase; it also caused broad inhibition spectrum against β-glucosidase and β-galactosidase. In contrast, the corresponding N -benzyl-l -DMDP cyclic isothioureas display selective inhibition of α-l -rhamnosidase; 3′, 4′-dichlorobenzyl-l -DMDP cyclic isothiourea (3r ) was found to display the most potent and selective inhibition of α-l -rhamnosidase, with IC50 value of 0.22 μM, about 46-fold better than the positive control 5- epi -deoxyrhamnojirimycin (5- epi -DRJ; IC50  = 10 μM) and occupied the active-site of this enzyme ( K i  = 0.11 μM). Bicyclic isothioureas of ido -l -DMDP did not inhibit α-l -rhamnosidase. These new mimics ofl -rhamnose may affect other enzymes associated with the biochemistry of rhamnose including enzymes involved in progression of tuberculosis.